Manipulating neuronal circuits with endogenous and recombinant cell-surface tethered modulators - Holford, Mandë; Auer, Sebastian; Laqua, Martin; Ibañez-Tallon, Ines (Frontiers in Molecular Neuroscience, 2009)
Neuronal circuits depend on the precise regulation of cell-surface receptors and ion channels. An ongoing challenge in neuroscience research is deciphering the functional contribution of specific receptors and ion channels using engineered modulators. A novel strategy, termed “tethered toxins”, was recently developed to characterize neuronal circuits using the evolutionary derived selectivity of venom peptide toxins and endogenous peptide ligands, such as lynx1 prototoxins. Herein, the discovery and engineering of cell-surface tethered peptides is reviewed, with particular attention given to their cell-autonomy, modular composition, and genetic targeting in different model organisms. The relative ease with which tethered peptides can be engineered, coupled with the increasing number of neuroactive venom toxins and ligand peptides being discovered, imply a multitude of potentially innovative applications for manipulating neuronal circuits and tissue-specific cell networks, including treatment of disorders caused by malfunction of receptors and ion channels.